Prospective Behavioral Study of Patients with Acute Respiratory Infections - Z. Sh. Nurmatov (Эпидемиология и вакцинопрофилактика, 2015)
Introduction: Review of official reports for the last 10 years revealed that up to 5% of the country population suffers from acute respiratory infections (ARI) annually. The study aimed to research the actual incidence by analyzing the prevailing behaviors in populations with respiratory symptoms.Methods: The prospective behavioral study was conducted at the outpatient clinic No 1 in Bishkek, with the number of catchment population aged above 18 totaling 25,057. Selection of respondents was based on systematic sampling. Every hundredth resident was selected from the electronic database of the catchment population. 224 people above 18 were actually enrolled in the study. The survey continued from November 2012 to April 2013. Except for the first interview, all follow-up interviews were done over the phone. For the purposes of the study, individuals in the study group were considered cases if they exhibited symptoms of ARI, according to the WHO Regional Office for Europe guidance for sentinel influenza surveillance in humans (2011). The survey results data analysis was performed using the Epi Info statistical software.Results: From November 2012, to April 2013, 61.2% (224) of the observed population became ill. 46.7% were ill with ARI once, 40.1% – 2 – 3 times, 11.7% – 4 – 7 times, as a result 137 people got sick a total of 307 times (136,161 per 100,000 population), only 75 cases sought medical attention (24.6%). The incidence rates in the observed group of patients with ARI (75/305) who sought medical care per 100,000 population comprised 33,482.1. According to the routine surveillance in 2012 – 2013 epidemic season, there were 34,637 cases of ARI (3,826.9 per 100,000 population). In the fall, the incidence totaled 36.8%, in winter – 20.2% and in spring 29.1%. The incidence rates by age group, gender, and presence of children in the family did not have statistically significant differences. The most frequent symptoms were as follows: cough (64.6%), rhinitis (61.0%), headache (58.1%), and sore throat (50.1%).Conclusions: In the 2012 – 2013 epidemic season, the incidence of ARI in the observed population was 35.6 times higher than the registered incidence in Bishkek, which indicates the low rate of seeking care.